Catecholamine Toxicity After Craniotomy Evacuation Craniotomy and Evacuation of The Abscess - Gibson Sirait, Ongta; Fadinie, Wulan (Journal of Society Medicine, 2022)
Increasing levels of endogenous catecholamines occur acutely to provide short-time adaptation to stressful conditions, known as the fight-or-fly response. Catecholamine toxicity requires multidisciplinary management. In this case, the patient is diagnosed with a brain abscess since birth. According of the history, physical examination and investigations, it was concluded that the diagnosis of epidural abscess with abscess evacuation craniotomy and PS ASA 2 (leukocytosis) with GA-ETT anesthesia. The operation is carried out with a duration of 4 hours. Vital sign monitoring obtained blood pressure sp108 – 125 62 - 90 mmHg, heart frequency 90 - 120 times per minute, 99% oxygen saturation. When in the recovery room, the patient experiences cardiac arrest, this is thought to result from catecholamine toxicity. Patients are treated as resuscitation in accordance with the algorithm of cardiac arrest in children. Patients experienced a response of spontaneous circulation (ROSC) and performed vital sign monitoring.